2016
DOI: 10.1007/s00464-016-5313-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lesion localisation at colonoscopy: outcomes from a multi-centre U.K. study

Abstract: BackgroundColonoscopy is currently the gold standard for detection of colorectal lesions, but may be limited in anatomically localising lesions. This audit aimed to determine the accuracy of colonoscopy lesion localisation, any subsequent changes in surgical management and any potentially influencing factors.MethodsPatients undergoing colonoscopy prior to elective curative surgery for colorectal lesion/s were included from 8 registered U.K. sites (2012–2014). Three sets of data were recorded: patient factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Next, was the rectosigmoid area which had over one fifth of the pathologies recorded. This trend is like findings in a study from the UK which showed a high correlation of colonoscopy pathology site with surgery findings [16].…”
Section: Discussionsupporting
confidence: 87%
“…Next, was the rectosigmoid area which had over one fifth of the pathologies recorded. This trend is like findings in a study from the UK which showed a high correlation of colonoscopy pathology site with surgery findings [16].…”
Section: Discussionsupporting
confidence: 87%
“…CT or even surgery 58,59 ; whether this could be extrapolated to a limited accuracy to define full cecal intubation, is likely, but finally unknown. In any case, we need more long-term follow-up studies from the various screening programmes on either primary screening colonoscopy or stool-based screening programmes to find out whether there is a clear predominance of right sided missed cancers.…”
Section: Online)mentioning
confidence: 99%
“…Colonoscopy combined with tattoo marking is the current gold standard for diagnosis and pre‐operative localisation of colorectal cancer. However, the accuracy of colonoscopy localisation varies between 59.7% and 98.3% with a recent prospective multi‐centre study reporting an 82% pre‐operative colonoscopy localisation accuracy rate 2 . Inaccurate localisations can alter surgical management, and this is reported to occur in 5.2%–6.3% of cases 2,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The current gold standard for identification and pre‐operative localisation is colonoscopy with tattoo marking. However, colonoscopy inaccurately localises 15%–21% of lesions and is highly dependent on many variables including operator skill 2–6 . Tattoo marking has higher localisation rates but can only be seen intra‐operatively.…”
Section: Introductionmentioning
confidence: 99%